The Impact of Cross-Platform Frameworks on Mobile Web Application Performance: A Systematic Review - Karin, Juliana (Universitas Komputer Indonesia, 2025)
As the demand for mobile applications surges, developers increasingly turn to cross-platform frameworks like React Native, Flutter, and Ionic to bypass the high costs of native development. However, a significant trade-off often exists between development efficiency and runtime performance. This systematic review investigates the impact of these frameworks on mobile web application performance, focusing on execution speed, memory management, and GPU utilization. By analyzing peer-reviewed literature from the last five years, this study identifies critical performance bottlenecks inherent in abstraction layers. The findings reveal that while Flutter nears native performance due to its direct rendering engine, JavaScript-based frameworks often suffer from bridge-related latency. This review provides a comprehensive synthesis of current performance benchmarks, offering developers a decision-making framework for selecting technologies based on computational requirements. Ultimately, the paper highlights the evolving landscape of mobile web apps and the closing gap between hybrid and native ecosystems.